Students’ Perception of Using Translanguaging Strategies in EFL Class Discussion - Sari, Meliya; Syafryadin, Syafryadin (Universitas Islam Negeri Raden Intan Lampung, 2024)
Many EFL students struggle to participate actively in classroom discussions due to limited proficiency in English, which can hinder their ability to fully engage and learn. The purpose of this study is to investigate students’ perceptions of language translation techniques used in EFL classroom discussions. The methodological technique used in this study is qualitative. Using qualitative descriptive methodologies, study data was gathered through interviews. Ten XI-grade students from a senior high school in Bengkulu were the subjects of the interview process. According to the results, students feel more at ease in class when their teachers employ translanguaging because it allows them to interact in two languages during class discussions, communicate with teachers effectively, engage in more engaging learning activities, and pick up new vocabulary. While some students acknowledged that they had trouble understanding teachers when they spoke in English, the majority of them understood the significance of English.